PENGIMPLEMENTASIAN DAN PERANCANGAN SISTEM INFORMASI PENJUALAN DAN PENGENDALIAN STOK BARANG PADA TOKO SWASTIKA SERVIS (SS) BANGUNAN DENGAN MENGGUNAKAN BAHASA PEMROGRAMAN VISUAL BASIC 6.0 DIDUKUNG DENGAN DATABASE MySQL - Sophan Sophian (Jurnal Momentum ISSN 1693-752X)
From the research that has been done on Swastika Stores Service (SS) Building Information System of Sales and stock control, which the purpose this researchis to gather information, and this information will be analyzed to determine the real problems faced of Swastika Shop Services (SS ) Building. After analyzing, the constraints faced in Stores Swastika Service (SS) Building the slow process in making sales and inventory reports. At the store transaction data recording process and the stocks still manually, allowing the error in data processing.Once learned, the authors draw the conclusion that in applying the computerized system in this case, Programming Language Visual Basic 6.0 and Database MySQL is the appropriate application, because these applications is very easy in the process of transactions and reports.